2014
DOI: 10.1177/194008291400700102
|View full text |Cite
|
Sign up to set email alerts
|

Density, Abundance and Activity Patterns of the Endangered Tapirus Bairdii in One of its Last Strongholds in Southern Mexico

Abstract: Baird´s tapir (Tapirus bairdii) is one of the most emblematic mammalian species from Mesoamerica. Due to its level of evolutionary distinctiveness and anthropogenic threat this species was recently ranked in 34th position, in terms of its urgency for conservation, among more than 4,000 species of mammals assessed by experts from the Zoological Society of London. Despite its evolutionary and conservation relevance there remain important gaps in knowledge of the basic ecology of this species. Based on camera-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 43 publications
1
27
0
2
Order By: Relevance
“…Tapirella bairdii is a solitary animal that can exhibit both diurnal and nocturnal behavior, even though several studies showed that they tend to be more active at night and crepuscular periods (Carbajal-Borges et al 2014), probably because of the difficulty to dissipate the body heat, a situation that is common to all large animals (Randall et al 1998;Foerster and Vaughan 2002). According to this, Tapirella bairdii would avoid the hottest hours of the day and restrict their movements to the cool hours of the day (Padilla and Dowler 1994;Foerster and Vaughan 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Tapirella bairdii is a solitary animal that can exhibit both diurnal and nocturnal behavior, even though several studies showed that they tend to be more active at night and crepuscular periods (Carbajal-Borges et al 2014), probably because of the difficulty to dissipate the body heat, a situation that is common to all large animals (Randall et al 1998;Foerster and Vaughan 2002). According to this, Tapirella bairdii would avoid the hottest hours of the day and restrict their movements to the cool hours of the day (Padilla and Dowler 1994;Foerster and Vaughan 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Naranjo‐Piñera () estimated 0.6 individuals/km 2 in Corcovado National Park in Costa Rica using transects, while our model estimates a mean of 0.81 individuals/km 2 in the same protected area. Carbajal‐Borges, Godínez‐Gómez, and Mendoza () cite 0.12 individuals/km 2 as their estimate for tapir abundance in the core area of El Triunfo Biosphere Reserve (though the estimates range up to 0.49 using different assumptions), while our model estimates a mean of 0.40 individuals/km 2 across the core area of the reserve. Mejía‐Correa, Diaz‐Martinez, and Molina () estimate 1.02 individuals/km 2 in Los Katíos National Park of Colombia, while our model estimates a mean of 0.65 individuals/km 2 in the same protected area.…”
Section: Resultsmentioning
confidence: 69%
“…Lizcano & Cavelier (2000) support this assertion; they indicate a movement of tapirs from paramo (a high Andean ecosystem) towards lower altitudes, stimulated by the development of farming and livestock grazing areas associated with human settlements. Carbajal-Borges et al (2014) confirmed the influence of anthropic intervention on the activity patterns of Baird's tapir (Tapirus bairdii). For them, this species showed mostly crepuscular activity and diurnal activity in areas providing the animals with a highly protected habitat.…”
Section: Universitas Scientiarum Vol 22 (1): 9-29mentioning
confidence: 55%